Bank recovery and resolution - Schelo, Sven (Alphen aan den Rijn, the Netherlands : Kluwer Law International, 2015)
Since 2008, enormous efforts have been made worldwide to draft rules to prevent a reoccurence of the devastating financial effects of that year. In the process, bank business has been laid open to intense public and government scrutiny, and regulation of banking has grown to spectacular proportions. Prominent among the measures taken is the EU Bank Recovery and Resolution Directive (BRRD), which, together with the Single Resolution Mechanism (SRM) and the Single Resolution Fund, constitutes a crucial new pillar in the European Banking Union. The presentation is enhanced by a comparative dimension, which includes reference to U.S. and other national developments and a full-scale analysis of Switzerland's regulatory response to the crisis.
Includes bibliographical references (pages 199-213) and index.
Keywords: Financial services industry -- Law and legislation; Financial services industry -- Law and legislation -- European Union countries; Financial crises -- Prevention; Global Financial Crisis, 2008-2009.